Perceived barriers to early goal-directed mobility in the intensive care unit: Results of a quality improvement evaluation. Issue 3 (May 2022) - Parker, Ann M.; Akhlaghi, Narges; Malik, Albahi M.; Friedman, Lisa Aronson; Mantheiy, Earl; Albert, Kelsey; Glover, Mary; Dong, Sherry; Lavezza, Annette; Seltzer, Jason; Needham, Dale M.
Abstract: Background: A multicentre randomised trial demonstrated improved outcomes for intensive care unit (ICU) patients using early, goal-directed mobility implemented by nurses. Objectives: The aim of the study was to evaluate barriers to nursing mobility, using a validated survey, during an ongoing quality improvement (QI) project (2019) in a medical ICU and determine changes from the pre-QI (2017) baseline. Methods: Nurses, nurse practitioners, physician assistants, and clinical technicians completed the 26-item Patient Mobilization Attitudes and Beliefs Survey for the ICU (PMABS-ICU). An overall score and three subscale scores (knowledge, attitudes, behaviour), each ranging from 0 to 100, were calculated; higher scores indicated greater barriers. Results: Seventy-five (93% response rate) nurses, eight (100%) nurse practitioners and physician assistants, and 11 (100%) clinical technicians completed the PMABS-ICU. For all respondents (N = 94), the mean (standard deviation) overall PMABS-ICU score was 32 (8) and the knowledge, attitudes and behaviour subscale scores were 22 (11), 33 (11), and 34 (8), respectively. Among all respondents completing the survey in both 2017 and 2019 (N = 46), there was improvement in the mean (95% confidence interval) overall score [−3.1 (−5.8,  −0.5); p = .022] and in the knowledge [−5.1 (−8.9, −1.3); p = .010] and attitudes [−3.9 (−7.3, −0.6); p = .023] subscale scores. Among all respondents (N = 48) taking the PMABS-ICU for the first time in 2019 compared with those taking the survey before the QI project in 2017 (N = 99), there was improvement in the mean (95% confidence interval) overall score [−3.8 (−6.5, −1.1); p = .007] and in the knowledge [−6.9 (−11.0, –2.7); p = .001] and attitude [−4.3 (−8.1, –0.5); p = .027] subscale scores. Conclusions: Using a validated survey administered to ICU nurses and other staff, before and during a structured QI project, there was a decrease in perceived barriers to mobility. Reduced barriers among those taking the survey for the first time during the QI project compared with those taking the survey before the QI project suggests a positive culture change supporting early, goal-directed mobility implemented by nurses.